2021
DOI: 10.25248/reas.e5410.2021
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco, proteção, diagnóstico e tratamento da depressão pós-parto no contexto da atenção primária

Abstract: Objetivo: Buscar informações acerca dos fatores de risco e de proteção para a DPP, formas de diagnóstico e tratamentos, indicando, assim, os níveis de evidência nas pesquisas. Métodos: Trata-se de uma revisão bibliográfica baseada em estudos publicados de 2015-2020, nas bases de dados PubMed, Literatura latino-americana e do caribe em ciências da saúde (LILACS) e Scientific Electronic Library Online (Scielo). Resultados: Foram identificados 96 estudos, desses, 12 foram selecionados com base nos critérios de in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…There was also an association between lower economic classification and PND symptoms. Studies show that inadequate living conditions resulting from poverty and low socioeconomic status are risk factors for PND (Öztora et al, 2019;Campos et al, 2021), which corroborates our findings. The study developed by Öztora et al (2019) with 111 Turkish mothers showed that 28.6% of mothers with PND had unemployed husbands and 21.4% had an income below minimum wage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was also an association between lower economic classification and PND symptoms. Studies show that inadequate living conditions resulting from poverty and low socioeconomic status are risk factors for PND (Öztora et al, 2019;Campos et al, 2021), which corroborates our findings. The study developed by Öztora et al (2019) with 111 Turkish mothers showed that 28.6% of mothers with PND had unemployed husbands and 21.4% had an income below minimum wage.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies corroborate the findings of Martínez et al (2016) and with the present manuscript regarding the maternal years of schooling, pointing out that the lower the level of education of the mothers, the greater the risk factor for the development of depressive symptoms is (Campos et al, 2021;Hartmann et al, 2021;Hartmann et al al., 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Igualmente, as mudanças no status socioeconômico, como perda de emprego, dificuldades financeiras ou redução da renda, podem ser fatores estressantes que contribuem para o desenvolvimento da depressão. Essas mudanças podem afetar a autoestima, a sensação de segurança e a capacidade de lidar com as adversidades, aumentando a vulnerabilidade à depressão [46].…”
Section: Idosos Não Institucionalizadosunclassified
“…According to Campos et al (2021), there was positive evidence regarding cognitive behavioral therapy in the puerperal period in these patients, which facilitated the self-knowledge of these pregnant women, consequently, the ability to deal with the symptoms. Pharmacological treatment may vary according to the degree of psychiatric disorder presented in each patient.…”
Section: Consequencesmentioning
confidence: 99%
“…(GUEDES-SILVA et al, 2003). Selective serotonin and noradrenaline inhibitors (SNRIs), Venlafaxine, are recommended for women who breastfeed, while for those who do not breastfeed, treatment similar to that of an adult with depression can be followed (CAMPOS, et al, 2021).…”
Section: Consequencesmentioning
confidence: 99%